Socialization of Processing Animal Products into Nugget as a Support for Creativity and Entrepreneurship at Dangau Datuk Bengkulu Agribusiness Vocational School - Gusriani, Ika (Fakultas Teknologi dan Industri Pangan Unisri Surakarta, 2024)
Dangau Datuk Bengkulu Agribusiness Vocational School is a Vocational High School that aims to produce graduates with professional and competent skills in the field of work in business and industry or to open independent businesses. In line with this goal, it is necessary to develop independent businesses by utilizing local potential both from animals and plants to become products with high economic value, one of which is the production of nuggets. Nuget is a preferred snack food because it has a good taste, and is easy to prepare, using chicken meat as a raw material. Chicken nuggets have the characteristics of high-fat content with low fiber. The problem of high-fat content and low fiber can be anticipated by using different raw materials, including using other sources of animal protein such as fish or shellfish, besides that you can also use several types of vegetables and jackfruit straw as a high-fiber food source. The development of nuget by utilizing animal and vegetable protein sources is expected to be one of the product development efforts for self-sufficiency and to increase the entrepreneurial abilities of Dangau Datuk Vocational High School students. This service is implemented through socialization and guidance on the process of processing nuggets from fish (catfish) and vegetables (tomatoes, potatoes, jackfruit straw) along with good packaging methods and labeling of the resulting nugget products. The conclusion of the implementation of this service is to increase students' understanding regarding the nutrition of raw material for nuget products, understanding the processing of nuget which are high in protein and rich in fiber, and increasing knowledge related to product packaging and labeling.